Oxidative potential of size-segregated particulate matter in the dust-storm impacted Hotan, northwest China. (1st July 2022) - An, Juqin; Liu, Huibin; Wang, Xinming; Talifu, Dilinuer; Abulizi, Abulikemu; Maihemuti, Mailikezhati; Li, Kejun; Bai, Haifeng; Luo, Ping; Xie, Xiaoxia
Abstract: Reactive oxygen species (ROS) induced by particulate matter (PM), of which OH is the most active free radical, have adverse health effects; however, PM-induced generation of ROS and OH has not been quantified and studied in northwest China, which suffers from severe dust storms. In this study, ambient PM10 and PM2.5 collected from the urban area of Hotan in the Uygur Autonomous Region of China, during dust and non-sand periods in 2020. ROS and OH were quantified and examined using the dichlorofluorescein diacetate (DCFH) assay and fluorescent probe method. The results showed that the oxidation potential (OP) of PM in the non-dust period (PM2.5 : 7.77 ± 0.29 nmol H2 O2 m −3 ; PM10 : 8.9 ± 0.38 nmol H2 O2 m −3 ) was higher than in the dust period (PM2.5 : 1.14 ± 0.71 nmol H2 O2 m −3 ; PM10 : 1.85 ± 0.77 nmol H2 O2 m −3 ). Compared to PM10, PM2.5 with larger specific surface area is more likely to adsorb the components contributing to ROS generation, so the induction amount of ROS and OH per unit volume in the environment will increase with increasing PM2.5 concentration. There was a weak correlation between O3 and ROS concentrations in the PM during the day, suggesting that photochemical reactions were a moderating factor in the formation of daytime ROS. In PM2.5, ROS showed a weak correlation with Pb, Cu, and Fe during the dust period. During the non-dust period, significantly correlated with Fe, Cu, and Cd ( P < 0.01; P < 0.05). In PM10, ROS correlated significantly with As ( P < 0.05) but weakly with Fe and Pb during the dust period. During the non-dust period, significantly correlated with As and Cd ( P < 0.01; P < 0.05) and weakly correlated with Ni, Cu, and Fe. This indicates that increasing trace metal levels can increase the OP of atmospheric PM. Highlights: The oxidation potential in the non-sand period was higher than that in the dust period. Oxidation potential per unit volume: PM10 >PM2.5 Photochemical reactions were a moderating factor in the formation of daytime ROS. The metals in the particles were beneficial for increasing the oxidation potential.